Reinforced Concrete Beam with Openings Strengthened Using CFRP Sheet - Win Win Stevanus; Noorwirdawati binti Ali (Jurnal Mahasiswa Jurusan Teknik Sipil, 2023)
Reinforced concrete is widely used in numerous parts of buildings, like columns, beams, and slabs. The material contains concrete that provides great compression strength, while steel reinforcement embedded in concrete has great tension strength. The failure of reinforced concrete beams with openings mainly located around the openings. Therefore, strengthening around the opening is required to increase the strength of the beam. In this study, Carbon Fiber Reinforced Polymer (CFRP) sheets are chosen. CFRP are composite materials that consist of carbon fiber with a resin to create material that has higher performance properties compared to each material separated. CFRP sheet provides superiority compared to steel-reinforced concrete that is still used, such as durability and reliability of the materials. This research objected to acknowledging the pattern of failure of reinforced concrete beams using ABAQUS, finite element modeling software in some cases. Finite Element Method (FEM) are used in this study by ABAQUS software and validate with experimental results. ABAQUS are used to simulate the model using Finite Element Method (FEM). From this study, beam with circular opening strengthened using CFRP have increase of 16.00% and the beam with 2 openings is increasing by 35.00%. The crack pattern of the beam without an opening is concentrated in the mid-span of the beam with a flexural failure, while the other specimen has a shear failure within circular openings. Significant improvements in ultimate load conclude that using CFRP sheet to strengthen beam with circular openings are suitable. The results of load-deflection profile calculated by Finite Element Modeling much higher than experimental results. The differences ultimate load results of Finite Element Method and Experimental are ranged from 2.94% until 9.87%. Keywords: RC Beam, Openings, CFRP sheet, CFRP composite, Finite Element Analysis (FEA), Finite Element Modelling (FEM), ABAQUS